168k views
5 votes
The product of (x+y)(8x-5y)

1 Answer

5 votes
Simplifying8x + -5y + -1x + 9 + -1y = 0
Reorder the terms:9 + 8x + -1x + -5y + -1y = 0
Combine like terms: 8x + -1x = 7x9 + 7x + -5y + -1y = 0
Combine like terms: -5y + -1y = -6y9 + 7x + -6y = 0
Solving9 + 7x + -6y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9' to each side of the equation.9 + 7x + -9 + -6y = 0 + -9
Reorder the terms:9 + -9 + 7x + -6y = 0 + -9
Combine like terms: 9 + -9 = 00 + 7x + -6y = 0 + -97x + -6y = 0 + -9
Combine like terms: 0 + -9 = -97x + -6y = -9
Add '6y' to each side of the equation.7x + -6y + 6y = -9 + 6y
Combine like terms: -6y + 6y = 07x + 0 = -9 + 6y7x = -9 + 6y
Divide each side by '7'.x = -1.285714286 + 0.8571428571y
Simplifyingx = -1.285714286 + 0.8571428571y
User Chemitaxis
by
5.4k points